Integrasi Life Skills Education dalam Pembelajaran Sejarah - Muadz Assidiqi; Sariyatun Sariyatun; Hieronymus Purwanta (Universitas Negeri Padang, 2023)
Education is an effort of knowledge in human nature to have various beneficial skills for the future. One by-type of this education is life skills education. Furthermore, education requires an actualization process through activities such as history learning. History learning is a process of a causal relationship between the past, present, and future to improve students’ soft skills. Thus, the method used in this research is qualitative with an instrumental case study approach at SMA N 1 Boyolali to provide an overview of the integration of life skills education in history learning. Data sources in this article are interviews, questionnaires, observations, and documentation. The data obtained analyze through interactive data analysis with the Nvivo 12 Pro software application in data reduction and display data. The article concludes that the integration of life skills education in history learning can improve students' soft skills consisting of personal, interpersonal, and cognitive skills.